Comprehensive Analysis of Moodle Activity Recommendations considering Complex Thinking Theory for Enhancing Learning Outcomes - Oliveira, Gustavo P.; Fernandes, Márcia A.; Maissiat, Jaqueline; Costa, Newarney T. da (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na Educação, 2024)
In the rapidly evolving landscape of digital technologies, e-learning and blended learning face the challenge of delivering personalized teaching experiences. This paper investigates the effectiveness of Moodle activity recommendations, aligned with complex thinking theory, in enhancing teaching personalization. The study utilized a methodology that assessed student engagement, performance, and self-identification across seven crucial skills defined by the theory. Student profiles were evaluated in a course’s initial module using activities embodying these characteristics, followed by personalized recommendations in subsequent modules. The analysis revealed a strong correlation between the proposed activities and improvements in academic performance, particularly in areas such as transdisciplinarity and metacognition. The findings highlight that students who engaged more actively with the recommended activities demonstrated significant improvements in their final grades.